ENHANCHING DISASTER PREPAREDNESS THROUGH GAMIFICATION: THE MISSION: RESILIENCE PROGRAM IN KENDARI CITY HIGH-RISK SCHOOLS - Saptaputra, Syawal Kamiluddin; Salsabila, Syefira; Akifah, Akifah; Mustaqim, Mustaqim; Ramadhan, Muh. Rahmat; Sagala, La Ode Hasnuddin S. (Abdi Dosen : Jurnal Pengabdian Pada Masyarakat, 2024)
This study aims to enhance disaster preparedness knowledge and skills among high school teachers and students in Kendari, Southeast Sulawesi, through a gamified educational approach called "Mission: Resilience." With the recognition of Kendari as a high-risk area for earthquakes, floods, and landslides, the project leverages gamification to improve engagement and learning outcomes in disaster readiness. The research involves a Participatory Rural Appraisal method, employing quizzes, flashcards, and simulations to deliver training on hazard mitigation, emergency response, and evacuation processes. Results from the pre and post-tests indicate a significant increase in disaster preparedness awareness and skills among participants. Additionally, the study confirms the effectiveness of integrating practical disaster simulations within the school curriculum. Ultimately, "Mission: Resilience" serves as a model for sustainable educational practices in disaster-prone regions, emphasizing continuous training and infrastructure enhancement to ensure long-term community resilience.